Increased prevalence of posttraumatic stress disorder in CRPS - Speck, V.; Schlereth, T.; Birklein, F.; Maihöfner, Christian (European Journal of Pain, 2017)
BACKGROUND: Although specific psychological disorders in complex regional pain syndrome (CRPS) have not been identified, studies suggest that CRPS patients may have increased rates of traumatic life events. Because these events do not always lead to apparent psychological symptoms, we systematically screened CRPS patients for posttraumatic stress disorder (PTSD) to determine if PTSD could be a risk factor for CRPS. METHODS: Consecutive CRPS patients referred to two university hospital centres (University of Erlangen, UMC Mainz) between December 2011 and April 2013 were prospectively examined using a diagnostic PTSD instrument (Post-traumatic Stress Diagnostic Scale (PDS). We also tested maladaptive coping strategies (brief-COPE inventory) and the PDS severity score as predictors for CRPS. Patients with non-CRPS extremity pain and healthy individuals were used as control groups. RESULTS: We collected data from 152 patients with CRPS, 55 control patients and 55 age- and sex-matched healthy individuals. Fifty-eight CRPS patients (38%), six non-CRPS pain patients (10%) and two healthy individuals (4%) met diagnostic criteria for PTSD. Initial PTSD symptom onset was prior to CRPS in 50 CRPS patients (86%) and during the course of CRPS in eight patients. Results of a logistic regression revealed that the PTSD severity score was associated with CRPS (p < 0.0001). Maladaptive coping strategies (p < 0.0001) were related to PTSD. CONCLUSIONS: posttraumatic stress disorder (PTSD) is more frequent in patients with CRPS than it is in the general population. SIGNIFICANCE: Research has not yet provided support for specific psychological predictors for CRPS.
EVALuna2:36547